2020
DOI: 10.1088/1361-6455/ab94c7
|View full text |Cite
|
Sign up to set email alerts
|

Metastable fragment production in electron–methanol collisions

Abstract: Dissociative excitation of methanol (CH3OH) by electron impact leading to the production of O(1S) and CO(a3Π) has been studied in the energy range from threshold to 100 eV using a unique detector which is selectively sensitive to low energy metastable particles. Time of flight techniques are used to separate atomic and molecular fragment species. Energy considerations have allowed certain excitation channels producing O(1S) to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Unfortunately, experimental data on the fragmentation dynamics of CH 3 OH by ND following electron impact, i.e., the kind of formed fragments, their formation thresholds, and formation cross sections, are very sparse. Dech et al reported a threshold of 13 eV for the production of O­( 1 S) in crossed beam experiments . From thermodynamic considerations, the authors concluded that O­( 1 S) is likely formed by decomposition of CH 3 OH into CH 3 • , H • , and O­( 1 S).…”
Section: Discussion Of the Reaction Mechanismmentioning
confidence: 99%
“…Unfortunately, experimental data on the fragmentation dynamics of CH 3 OH by ND following electron impact, i.e., the kind of formed fragments, their formation thresholds, and formation cross sections, are very sparse. Dech et al reported a threshold of 13 eV for the production of O­( 1 S) in crossed beam experiments . From thermodynamic considerations, the authors concluded that O­( 1 S) is likely formed by decomposition of CH 3 OH into CH 3 • , H • , and O­( 1 S).…”
Section: Discussion Of the Reaction Mechanismmentioning
confidence: 99%
“…However, there are only a few reports in which this type of detector was used. For example, in one recent study, such detectors were used to investigate metastable fragments, i.e., O( 1 S) and CO(a 3 Π), formed through to the dissociative excitation of methanol in the electron energy range from their appearance energy to 100 eV [135].…”
Section: Neutral Detection By Other Techniquesmentioning
confidence: 99%